2005
DOI: 10.1080/08958370590922625
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Sulfur Dioxide Inhalation on Cytokine Levels in Lungs and Serum of Mice

Abstract: In order to elucidate the immunotoxic mechanism exerted by sulfur dioxide (SO(2)), we investigated the effect of SO(2), a major air pollutant, on the cytokine levels in lungs and serum of male mice. Levels of interlukin-6(IL-6), tumor necrosis factor-alpha (TNF-alpha), and transforming growth factor-beta1 (TGF-beta1) in lungs and serum from male mice exposed to SO(2) at various concentrations were measured by the enzyme-linked immunosorbent assay. Sixty Kunming albino male mice were divided randomly into six e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
29
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 22 publications
1
29
0
Order By: Relevance
“…21, 22 Besides, there were significant increased IL-6 and tumor necrosis factor-a levels in lung tissues of SO 2 inhaled mice. 23 In our study, we also confirmed the effects of sodium sulfite toward airway inflammation. The total inflammatory scores were higher in sIN and mIN ĂŸ sIN groups.…”
Section: Discussionsupporting
confidence: 89%
“…21, 22 Besides, there were significant increased IL-6 and tumor necrosis factor-a levels in lung tissues of SO 2 inhaled mice. 23 In our study, we also confirmed the effects of sodium sulfite toward airway inflammation. The total inflammatory scores were higher in sIN and mIN ĂŸ sIN groups.…”
Section: Discussionsupporting
confidence: 89%
“…Apoptosis can be initiated by diverse signals and executed via diVerent biochemical pathways (Hengartner, 2000). In previous studies, SO 2 inhalation caused increase of levels of tumor necrosis factor (TNF-) and transforming growth factor-1 (TGF-1) (Meng et al, 2005b). These factors play pivotal roles in many biological processes in mammalian cells, including apoptosis (Ashley et al, 1998;Zhang, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In mammalian cells, sulfur dioxide and Na 2 SO 3 have been associated with marked changes in ROS and activation of redox pathways [46][47][48][49]. In addition to the significant increases in glutathione synthetase and sulfiredoxin, superoxide dismutase and selenoprotein-S increased and NADPH oxidase declined significantly.…”
Section: Discussionmentioning
confidence: 99%